Assessment of Ultrasound Velocity Application for Chemical Process Monitoring - Svilainis, Linas; Rodriguez, Alberto; Liaukonis, Dobilas; Chaziachmetovas, Andrius (Elektronika ir Elektrotechnika, 2015)
Study on the accuracy of the ultrasound velocity application for chemical process monitoring is presented. Cure degree of epoxy resins was monitored in order to establish the percentage of the final cure based on ultrasound velocity of longitudinal waves. Time of flight estimations by correlation processing were used to estimate the velocity. Sources of error in the velocity measurement and their influence in the sensitivity and accuracy of the results have been studied. In order to improve the accuracy and reliability of the measurements, the use of Spread Spectrum instead of conventional excitation signals have been evaluated. Experimental results indicate that random errors of propagation time estimation are lower than velocity fluctuation over the chemical process. Spread spectrum signals provide more reliable measurements. DOI: http://dx.doi.org/10.5755/j01.eee.21.4.12783